2015
DOI: 10.1136/bmj.h770
|View full text |Cite
|
Sign up to set email alerts
|

School based education programme to reduce salt intake in children and their families (School-EduSalt): cluster randomised controlled trial

Abstract: Objective To determine whether an education programme targeted at schoolchildren could lower salt intake in children and their families. Design Cluster randomised controlled trial, with schools randomly assigned to either the intervention or control group. Setting 28 primary schools in urban Changzhi, northern China. Participants 279 children in grade 5 of primary school, with mean age of 10.1; 553 adult family members (mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
225
1
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(249 citation statements)
references
References 32 publications
4
225
1
11
Order By: Relevance
“…This approach was used by He and colleagues to evaluate a school based education programme aimed at reducing salt intake in children and their families (box 1). 4…”
Section: Approaches To Analysismentioning
confidence: 99%
“…This approach was used by He and colleagues to evaluate a school based education programme aimed at reducing salt intake in children and their families (box 1). 4…”
Section: Approaches To Analysismentioning
confidence: 99%
“…56 The China Salt Substitute Study demonstrated, among 608 individuals with high cardiovascular risk from rural northern China, after 12 months of intervention with salt substitute, systolic blood pressure was significantly reduced by 5.4 mm Hg (P=0.001) on average in comparison with the regular salt group. 57 The blood pressure lowering effect of salt substitute has been reconfirmed in trials in patients with hypertension in other Chinese populations.…”
Section: Changes In Lifestylementioning
confidence: 99%
“…The examples of implementation research in prevention and control of CVD in China include the Simplified Cardiovascular Management Study (SimCard), 178 school based education programme to reduce salt intake in children and their families (School EduSalt), 56 China Rural Health Initiative (CRHI) 179, 180 , CPACS, 181, 182 China Da Qing Diabetes Prevention Study, 183 etc. 184 For example, the recently completed SimCard trial demonstrated that a simplified cardiovascular management program, only two drugs (anti-hypertensive and aspirin) and two lifestyle recommendations (smoking cessation and salt reduction), delivered by community health workers with the aid of a smartphone-based electronic decision support system, was effective 178 .…”
Section: Future Directionsmentioning
confidence: 99%
“…In parallel to national initiatives smaller scale salt-reduction interventions have been shown to be effective in reducing salt intake. For example, a recent school-based educational intervention was shown to reduce salt consumption of both the children exposed to the intervention and their families (16). The lack of national salt-reduction initiatives in low-to middleincome countries, such as Lebanon, could be attributed to limited funding and organizational infrastructure at governmental level.…”
Section: Introductionmentioning
confidence: 99%